Impact of Apolipoprotein(a) Isoform Size Heterogeneity on the Lysine Binding Function of Lipoprotein(a) in Early Onset Coronary Artery Disease - Simó, Josep M.; Joven, Jorge; Vilella, Elisabet; Ribas, Montserrat; Pujana, Miguel A.; Sundaram, Indirana M.; Hammel, Jeffrey P.; Hoover-Plow, Jane L. (Thrombosis and Haemostasis, 2001)
Elevated plasma Lp(a) is an independent risk factor for cardiovascular disease. Unique to Lp(a) is the apoprotein, apo(a) which can vary from 250 to 800 kDa in molecular weight. Small isoforms are also associated with the risk of cardiovascular disease. The purpose of this study was to examine the association of Lp(a) concentration, apo(a) size, and Lp(a) lysine-binding site(s) (LBS) function in patients with early onset heart disease, and age-matched controls. Mean values of Lp(a) were significantly higher in the patients than for the age-matched group. The smallest molecular weight isoform for each subject had significantly fewer kringles for the patients than the age-matched controls. There was a significant correlation between LBS activity and kringle number in the single-banded phenotypes of the patients, but not the controls. LBS activity was significantly higher in patients with small isoforms (≤18 kringles) compared to controls. The odds ratio for coronary artery disease for high LBS activity and high Lp(a) concentration was 4.4 (p = 0.002) and for high LBS activity and small isoforms was 10.1 (p = 0.002). In the patients, Lp(a) concentration was higher, apo(a) size was smaller, and LBS activity higher in the small isoforms compared to the controls. This study suggests an association of high LBS activity in small isoforms of Lp(a) with disease in humans.
Keywords: Lipoprotein(a); apo(a) size; lysine binding site function; myocardial infarction